Easy surveillance of muscle volume decline in chronic liver disease patients using finger‐circle (yubi‐wakka) test. Issue 2 (21st February 2019) - Hiraoka, Atsushi; Izumoto, Hirofumi; Ueki, Hidetaro; Yoshino, Takeaki; Aibiki, Toshihiko; Okudaira, Tomonari; Yamago, Hiroka; Suga, Yoshifumi; Iwasaki, Ryuichiro; Tomida, Hideomi; Mori, Kenichiro; Miyata, Hideki; et al.
Abstract: Background: Muscle atrophy (MA) and muscle strength decline are important clinical features in chronic liver disease (CLD) patients. An easy to perform MA screening method without need for special equipment would be helpful. We evaluated the usefulness of the previously reported finger‐circle test as screening for MA in CLD patients. Methods: We retrospectively enrolled 358 Japanese CLD outpatients (70.8 ± 10.2 years, male/female = 234/124) who had undergone a computed tomography examination from December 2017 to March 2018, of whom 137 had chronic hepatitis, 169 had liver cirrhosis Child–Pugh A, and 52 had liver cirrhosis Child–Pugh B/C. Bilateral psoas muscle area at the middle of the third lumber vertebra (L3) was evaluated with computed tomography findings, which was performed as a screening of hepatocellular carcinoma, using a previously reported parameter for MA [psoas index (PI): total psoas muscle area (cm 2 )/height (m) 2 ] [mean PI ± standard deviation (SD) of male patients: 6.50 ± 1.13 cm 2 /m 2 and those of female patients: 4.30 ± 0.90 cm 2 /m 2 ]. We then evaluated the correlation between MA and finger‐circle test results in these patients. Results: The mean PI values for finger‐circle test results Bigger, Just‐fits, and Smaller were 5.64 ± 1.34, 5.00 ± 1.25, and 4.83 ± 1.46 cm 2 /m 2, respectively, in male patients ( P < 0.001) and 4.31 ± 1.06, 3.93 ± 0.97, and 3.42 ± 0.94 cm 2 /m 2, respectively, in female patients ( P = 0.001). We found that a finger‐circle test result in male patients other than Bigger (Just‐fits and Smaller) predicted a decline in psoas muscle area of L3 to PI 5.25 cm 2 /m 2 (sensitivity/specificity 0.619/0.667, area under the curve 0.654, 95% confidence interval 0.583–0.724), which was approximately mean minus 1 SD (5.37 cm 2 /m 2 ). On the other hand, a Smaller test result in female patients predicted a decline in psoas muscle area of L3 to PI 3.33 cm 2 /m 2 (sensitivity/specificity 0.740/0.583, area under the curve 0.698, 95% confidence interval 0.583–0.813), approximately mean minus 1 SD (3.40 cm 2 /m 2 ). Conclusions: The finger‐circle test is an easy to perform and effective screening method for predicting earlier stage of MA in CLD patients without the need for special equipment.